2016
DOI: 10.1038/srep30079
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium-induced reduction of plant growth in alfalfa (Medicago sativa) is mediated by interrupting auxin transport and accumulation in roots

Abstract: The objective of this study was to investigate Al3+-induced IAA transport, distribution, and the relation of these two processes to Al3+-inhibition of root growth in alfalfa. Alfalfa seedlings with or without apical buds were exposed to 0 or 100 μM AlCl3 and were foliar sprayed with water or 6 mg L−1 IAA. Aluminium stress resulted in disordered arrangement of cells, deformed cell shapes, altered cell structure, and a shorter length of the meristematic zone in root tips. Aluminium stress significantly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 56 publications
(76 reference statements)
1
53
0
Order By: Relevance
“…Soil contains various toxic and non‐essential heavy metal elements including Cr, Cd, and Al, which affect various metabolic, developmental, and physiological processes in plants, leading to a reduction in leaf area, primary root elongation, and lateral and adventitious root development (Eleftheriou et al, ; López‐Bucio et al, ; Sun et al, ; Wang et al, ; Yuan & Huang, ). Cr stress also interferes with the uptake of essential elements, reduces germination rate, detriments the cellular ultrastructures, and represses mitotic cell division and cell elongation (Eleftheriou et al, ; Ortiz‐Castro et al, ; Shanker et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil contains various toxic and non‐essential heavy metal elements including Cr, Cd, and Al, which affect various metabolic, developmental, and physiological processes in plants, leading to a reduction in leaf area, primary root elongation, and lateral and adventitious root development (Eleftheriou et al, ; López‐Bucio et al, ; Sun et al, ; Wang et al, ; Yuan & Huang, ). Cr stress also interferes with the uptake of essential elements, reduces germination rate, detriments the cellular ultrastructures, and represses mitotic cell division and cell elongation (Eleftheriou et al, ; Ortiz‐Castro et al, ; Shanker et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene and auxin act synergistically to regulate root growth and development (Guo, Kong, & Yang, ; Marciniak, Glazinska, Kesy, & Tretyn, ; Muday et al, ), and inhibit primary root elongation in response to other exogenous stimuli, such as aluminum and alkaline stresses (Li, Xu, Liu, et al, ; Sun et al, ; Wang et al, ). The probability that ethylene and auxin participate collectively in plant responses to Cr(VI) was investigated in our study, which confirmed the crosstalk between ethylene and auxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfalfa (WL-525), which is an Al-tolerant cultivar [24, 25], was obtained from the National Seed Corporation (New Delhi, India). Healthy seeds of uniform size were surface-sterilized with 0.5% (v/v) sodium hypochlorite solution and repeatedly washed with double-distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In soils with 0.7 cmol/kg Al 3+ , root weight reduced by 35% to 73% (differed among cultivars) compared to those in soils with 0.02 cmol/kg Al 3+ (Khu et al, 2012). Root weight of alfalfa exposed to 100 μM AlCl 3 reduced by 56.1% than those in 0 μM AlCl 3 (Wang, Ren, Huang, Wang, Zhou, & An, 2016). In solutions with 2 mM AlCl 3 and 4 mM AlCl 3 , 12 from 13 alfalfa cultivars showed significant inhibition of biomass accumulation when compared to that in 0 mM AlCl 3 (Pan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%